The ultrasound technology for modifying enzyme activity - Lindsay, Meliza (2016)
Enzymes are protein complexes compounds widely studied and used due to their ability to catalyze reactions. The food processing mainly aims the inactivation of enzymes due to various undesirable effects. However, there are many processes that can be optimized by its catalytic activity. In this context, different technologies have been applied both to inactivate or to improve the enzymes efficiency. The Ultrasound technology emerges as an alternative mainly applied to achieve the enzyme inactivation. On the contrary, very few investigations show the ability of this technology under certain conditions to achieve the opposite effect (i.e. increase the catalytic activity of enzymes). The objective of this study was to correlate the ultrasonic energy delivered to the sample (J/mL) with the residual enzymatic activity and explain the possible mechanisms which results in the enzymatic activation/inactivation complex behavior. The activity of POD in coconut water was evaluated as a model. The enzymatic activity initially increased, followed by reduction with a trend to enzyme inactivation. This complex behavior is directly related to the applied ultrasonic energy and their direct mechanical effects on the product, as well as the effect in the enzymatic infinite intermediate states and its structural conformation changes. The obtained results are useful for both academic and industrial perspectives.